Economic Dynamics of Urban Fishermen in Muarareja: The Death of Fish Auction Places - Amanatin, Elsa Lutmilarita; Sekarningrum, Bintarsih; Supangkat, Budiawati (Sociology Department Of Syiah Kuala University, 2024)
This study examines the closure of the Fish Auction Place (TPI) in Muarareja, which was caused by debt agreements between fishermen and fish traders for boat purchases. The closure of the TPI has led to fishermen losing access to a competitive sales platform and becoming dependent on the traders' markets. The research method used was qualitative with a case study approach, through semi-structured interviews, direct observation, and documentation. The research participants included 6 skippers or fishermen who own ships, 5 crew members (ABK), 6 collectors or traders, and 3 mothers who make salted fish around the TPI. Data collection was carried out from June 1 to August 28, 2023. The purpose of the study was to analyze changes in the dynamics of patron-client relationships among fishermen in Muarareja and to examine the economic and social impacts of the closure of the TPI. The results showed that the closure of the TPI changed the mechanism of buying and selling fish to be more closed to patrons (traders), which significantly affected the social and economic dynamics of urban fishermen. Based on these findings, it is recommended to examine the effectiveness of alternative programs such as fishermen's cooperatives or micro-loans, and further research is needed on the revitalization of the TPI to improve the overall welfare of fishermen. In the context of public policy, it is also necessary to consider strategies that strengthen the capacity of fishermen in facing increasingly complex global economic challenges. This research is expected to provide significant theoretical and practical contributions to the field of sociology, especially economic sociology.